ZnO and MgZnO Nanocrystalline Flexible Films: Optical and Material Properties. (24th July 2011) - Huso, Jesse; Morrison, John L.; Che, Hui; Sundararajan, Jency P.; Yeh, Wei Jiang; McIlroy, David; Williams, Thomas J.; Bergman, Leah
Abstract : An emerging material for flexible UV applications isMg x Zn 1 − x O which is capable of tunable bandgap and luminescence in the UV range of 3.4 eV–7.4 eV depending on the composition x . Studies on the optical and material characteristics of ZnO and Mg0.3 Zn0.7 O nanocrystalline flexible films are presented. The analysis indicates that the ZnO and Mg0.3 Zn0.7 O have bandgaps of 3.34 eV and 4.02 eV, respectively. The photoluminescence (PL) of the ZnO film was found to exhibit a structural defect-related emission at 3.316 eV inherent to the nanocrystalline morphology. The PL of the Mg0.3 Zn0.7 O film exhibits two broad peaks at 3.38 eV and at 3.95 eV that are discussed in terms of the solubility limit of the ZnO-MgO alloy system. Additionally, external deformation of the film did not have a significant impact on its properties as indicated by the Raman LO-mode behavior, making these films attractive for UV flexible applications.